Understanding the Escalation of Brain Drain in Nigeria From Poor Leadership Point of View - Ojo, Omonijo Dare; Ugochukwu, Nnedum Obiajulu Anthony; Obinna, Ezeokana Jude (Richtmann Publishing, 2011)
Migration of people from one place to another in countries of the world in search of better conditions of living predates history.It ignited western societies’ contact with Africa and the rest of the world. Prior the contact, agriculture was the main stay of Africa’seconomy. Thus, the movement of farmers from one location to another in search of fertile grounds for cultivation was in vogue. Afterindependence in Nigeria, cattle rearers are known for relocating from the North to South during dry season in search of green grass tosustain their cattle and occupation. In the present day Nigeria, the same scenario still abounds but in a new dimension. It now involvesmovement of highly skilled manpower from the country to developed societies. Among other things, this paper finds out if there is arelationship between poor leadership of the country and escalation of brain drain. Simple percentage and ranking method was used toanalyze the study’s data. Chi-square was used to test its hypothesis. Our result revealed a relationship between poor leadership of thecountry and brain drain. It equally indicated that students are interested in travelling out of the country to developed societies after theirstudy. Also from the study, twelve causes of brain drain were indentified. Some of them are: mass unemployment, poor salaries andconditions of service, mass poverty, crises-religious, communal, political, education etc. In respect of effects of brain drain on the nation’seconomy, eleven factors were identified by the respondents. Some of them are: loss of human capital assets to man various institutions inthe country, loss of tax of migrated manpower to foreign countries, loss of capital invested in education of migrated manpower assets etc.Finally, eleven solutions were profiled to the lingering problem of brain drain. The most important ones are: Good leadership, salary andconditions of service as well as rewarding system for diligent staff, mass employment etc.